The Formation Stages of South Korea’s Soft Power Diplomacy in Central Asia (The Journal of Interdisciplinary Human Studies, 2026)
This article examines South Korea’s soft power policy, with particular emphasis on the content, stages of formation, and key directions of its soft power strategy in the Central Asian region. The study focuses on South Korea’s cultural diplomacy, education, humanitarian cooperation, official development assistance (ODA), as well as mechanisms of influence exercised through international institutions. The strategy is analyzed within the framework of neo-institutionalism and soft power theory, highlighting the interaction between state and non-state institutions and scientifically substantiating the impact of normative values and institutional mechanisms on regional political processes.
Keywords: soft power; KOICA; Koryo-saram; Hallyu; ODA; KOTRA; cultural diplomacy; people-to-people diplomacy; government-to-government diplomacy